Cephalothin as a Carrier of 6-Mercaptopurine for Targeting Cancer Tissues - H. Mohammad, Mohammad; J.Al-Karagully, Haider (Iraqi Journal of Pharmaceutical Sciences, 2017)
A lower extracellular pH is one of the few well-documented physiological differences between tumour and normal tissues. On the other hand, elevated glutathione (GSH) level has been detected in many tumours compared with healthy surrounding tissues. The compound II: 3-(9H-purin-6-yl-thio) carbonothionyl methyl-8-oxo-7-(2-thiophen-2-yl) acetamido-5-thia-1-azabicyclo-4-octo-ene-carboxylic acid was a cephalothin derivative contain 6-mercaptopurine (6-MP). Compound II react with general base catalysis in slightly acidic pH or with sulfhydryl nucleophiles to release the chemotherapeutic drug 6-MP. The generation of compound II was accomplished following multistep reaction procedures. The structure of compound II and its intermediate was confirmed by their melting point, infrared spectroscopy, CHN and NMR analysis. The hydrolysis of compound II in aqueous buffer solution of pH 6 and in the presence of GSH at pH 7.4 was studied. The partition coefficient (PC) of compound II was also determined. Compound II has acceptable rate of hydrolysis at slightly acidic medium pH 6 (t1/2 = 56.34 min.) and 80% of compound II had been converted to 6-MP within 30 min in the presence of GSH. And the compound has acceptable stability at pH 7.4(t0.5=639.65 min.) and the rate of hydrolysis was effected by change the buffer concentration. This compound can selectively deliver 6-MP into the tumour tissues which have acidic pH or elevated GSH level. Compound II had an improved PC value of 12.23 compared to 1.22 for free drug 6-MP confirming higher lipophilicity. Key words: 6-mercaptopurine, cancer, prodrug, targeting